Tourism attractions and development of Pangkor Island: a study of foreign tourists’ perceptions - Jabil Mapjabil,; Badariah Ab Rahman,; Mohamad Pirdaus Yusoh,; Mazdi Marzuki,; Mohd Zulhalmi Ibrahim,; Harifah Mohd Noor, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Island tourism is fast becoming popular among tourists, and for Malaysia this provides a fertile avenue for further extension of her tourism industry. This study examined the attractions and development of tourism in Pangkor Island, Perak as perceived by international tourists. A total of 125 male and female international tourists was administered with questionnaires to provide primary data for the study. The findings revealed the beaches as the the main attraction features (53.9%) followed by water recreational activities (5.8%), local food (4.5%), wildlife (3.9%), and low-cost, good accommodation and weather (1.9%, respectively). On the minus side, 36.25% of the respondents pointed to garbage and dirty coastal environment as major problems of Pangkor, besides the lack of beach facilities (21.3%). Nevertheless, field observations of foreign tourists’ activities in Pangkor showed that generally the foreign tourists were satisfied with the island’s tourism development as depicted by their snorkelling, banana boat ride, island hopping, sun bathing and trail hiking activities.